Consumer perception of the dermo cosmetics brand in the Czech Republic, Slovakia, and Hungary : case study L´Oréal Vichy - Lomenčíková, Nikola; Machek, Martin; Placek, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The main objective of this presented Master’s thesis is to analyse and identify the consumer perception of the chosen dermocosmetics brand belonging to the portfolio of L’Oréal group among the consumers falling into the age group of 20-35, in the scope of three elected CEE countries, Czechia, Slovakia and Hungary. To achieve this, the review of the relevant literature along with the secondary and primary research was conducted using appropriate combination of quantitative and qualitative research methods. The primary research comprised of nine in-depth interviews with the respondents in the selected age range from, originating from Czechia, Slovakia and Hungary, who identified themselves as regular dermocosmetics users. To further quantify the findings from the in-depth interviews, quantitative study was conducted in form of an online survey. After the data analysis, main results are discussed and recommendations for the Vichy marketing team are provided with respect to young segment, together with suggestions for further research on this topic. The results of the study have proved, that Vichy is still the leading dermocosmetics brand in the scope of the three analysed countries, however, its long-term leading position within the anti-age category negatively affects the perception of younger consumers, who strongly associate the brand with anti-age and less favourable brand associations, which should be addressed by the marketing team in Prague.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses